Investigation of the stress-strain state of the scraper traction frame - Nilov V.A.; Fedorov E.V. (Научно-технический вестник Брянского государственного университета)
The paper deals with the loading of the scraper traction frame in the traction and transport modes. When digging the soil, the case of transferring the traction force of the tractor directly to the ladle was examined, bypassing the traction frame. A favorable effect on the stress-strain state of the traction frame of the scraper of its unloading from the traction force of the tractor has been established.